Tumor-infiltrating lymphocytes: apparently good for melanoma patients. But why? - Cipponi, Arcadi; Wieers, Grégoire; van Baren, Nicolas; Coulie, Pierre G. (Cancer Immunology, Immunotherapy, 2011)
Tumor-infiltrating T lymphocytes (TILs) are observed in a number of human primary or metastatic tumors. Recently, gene expression profiling experiments suggested that the presence of T cells in metastatic melanomas before vaccinating the patients with tumor antigens could be a biomarker for clinical benefit from the vaccines. In this context, we review results pertaining to TILs in human melanomas, their prognostic value, and some possible reasons why their presence could help in selecting melanoma patients for vaccination against tumor-specific antigens.